Investigations on the role of various hemato-biochemical parameters on genital prolapse of cows - Sharma, Vivek; Kumar, Pravesh; Sharma, Akshay; Singh, Madhumeet (The Indian Journal of Animal Sciences, 2022)
The present study was designed for investigation on etiologies of genital prolapse in cattle of Himachal Pradesh. A total of 111 cattle were part of study, 39 were suffering with genital prolapse in pregnant, post-partum and non-pregnant stages of gestation while the remaining 72 cows were in normal pregnancy, post-partum and non-pregnant stage. Blood samples were collected for hormonal (cortisol, estrogen and progesterone), minerals (calcium, phosphorus and magnesium) and biochemical (glucose, total protein, triglycerides, urea, cholesterol, SGPT, SGOT) estimations. Mean plasma estradiol-17Î² elevation was significant (P<0.01) in affected cattle in all three stages (pregnant, postpartum and non-pregnant). Progesterone concentration was significantly (P<0.01) lower in affected cattle in pregnant and post-partum group. Also, significant elevation (P<0.01) was observed in cortisol plasma concentration among affected cattle in non-pregnant and post-partum groups. Calcium and phosphorus concentrations were significantly (P<0.01) lower in affected cattle with genital prolapse as compare to non-affected cattle in non-pregnant, pregnant and post-partum group. Similarly in the category of biochemical in affected pregnant group significant elevations were observed for triglyceride (P<0.01), urea (P<0.01) and SGOT (P<0.05). Post-partum group showed significant (P<0.05) decline in total protein, SGPT and SGOT. Whereas, in non-pregnant group, significant (P<0.05) increase and decrease was observed for urea and cholesterol concentration, respectively for prolapse showing cows. It is concluded that the serum hormones (estradiol and progesterone) and minerals (calcium and phosphorus) concentrations differ significantly between the genital prolapse affected and healthy cattle.